A high-temperature-resistant zwitterionic polymer tackifier for composite calcium salt completion fluid and a preparation method and application thereof
Patent Information
- Application Number
- CN202510337795.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-03-21
AI Technical Summary
[0006]针对现有技术的不足,尤其是现有高密度无固相完井液用增粘剂配伍性差,高温稳定性以及耐盐性不足的问题,本发明提供了一种复合钙盐完井液用抗高温两性离子聚合物增粘剂及其制备方法与应用
[0038]1、本发明两性离子增粘剂中引入的丙烯酰胺类单体,可以显著提升生成产物的分子量及抗温能力;引入的阴离子抗温单体中含有水化能力极强的磺酸基团,增强聚合物在高温条件下的稳定性;引入的抗温阳离子单体提供了阳离子基团,可以在聚合物分子链上形成稳定的五元环结构,进一步增强聚合物分子刚性;引入的两性离子单体A同时含有羧酸基团和铵根离子,可以形成电荷平衡,使产物具有“反聚电解质效应”,在高盐条件下,分子链进一步舒展,显著增加复合钙盐完井液的粘度,而且两性离子单体A中含有的α-甲基组会增大聚合物链之间的位阻,会使舒展的聚合物分子链进一步形成稳定的网状结构,显著提高聚合物分子在完井液中的流动阻力,从而达到提升完井液粘度的效果。
Smart Images

Figure BDA0005322249060000031 
Figure BDA0005322249060000061 
Figure BDA0005322249060000081
Abstract
Description
Technical Field
[0001] This invention relates to a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluids, its preparation method and application, belonging to the field of oilfield chemistry in the petroleum industry. Background Technology
[0002] Completion fluid technology is a major engineering challenge in oil and gas well completion. With increasing drilling depth, especially when deep wells encounter complex formations and large sections of shale, inaccurate understanding of formation characteristics and pressure profiles often leads to an inability to respond promptly to changes in reservoir properties, resulting in frequent blowouts and well kicks. Completion fluids must not only balance formation pressure, clean the wellbore, stabilize the wellbore, and control filtration and leakage, but also maintain good temperature resistance, salt resistance, and corrosion resistance. Solid-free completion fluids, due to their absence of solid particles and clay, can significantly reduce damage to the reservoir and have received widespread attention in recent years.
[0003] In solids-free completion fluids, viscosifiers are crucial core additives. Solids-free completion fluids themselves lack sufficient viscosity and shear strength, making it difficult to suspend cuttings and clean the wellbore. However, solids-free completion fluids with added viscosifiers can effectively suspend cuttings and reduce downhole fluid loss. When the bottomhole temperature exceeds 180℃, synthetic polymer viscosifiers are often used to improve the rheological properties of the completion fluid. However, most existing synthetic polymers are prone to coiling and agglomeration in high-concentration inorganic high-valent salt solutions (CaCl2, CaBr2, etc.), leading to polymer precipitation and damage to the completion fluid's performance.
[0004] Chinese patent document CN104650827A developed a temperature-resistant micro-crosslinked thickener, whose raw materials are alkenyl sulfonic acid, alkenyl amide, and alkenyl benzene. This thickener still has a good thickening effect after hot rolling aging at 165℃ for 16 hours, which is better than the foreign similar product HE300, but it cannot meet the higher temperature resistance requirements (≥180℃). Chinese patent document CN118459660A polymerized 2-acrylamido-2-methylpropanesulfonic acid, dimethylaminopropylacrylamide, sodium p-styrene sulfonate, hydrophobic monomers, and micro-crosslinking agents into a linear copolymer through an initiator, and blended it with a micron-scale inert crosslinking material to develop a high-temperature resistant polymer thickener for calcium chloride brine completion fluid with a temperature resistance of 170℃, but its performance fails above 180℃. Chinese patent document CN114214049A discloses a method for preparing a solid-free viscosity-enhancing workover fluid for ultra-deep, ultra-high temperature oil and gas wells. This method involves adding an ultra-high temperature polymer crosslinking agent, an ultra-high temperature polymer stabilizer, and an ultra-high temperature heat stabilizer to a thickener solution. This allows the completion fluid to maintain good performance even at temperatures above 180°C, meeting the requirement for stable viscosity-enhancing agent performance in high-temperature solid-free brine. However, the maximum density of the brine used is 1.3 g / cm³. 3 Furthermore, the added salt is a monovalent sodium salt, which does not meet the requirements for use in high-density completion fluids.
[0005] Therefore, how to enhance the stability of viscosifiers for solid-free completion fluids in high-temperature, high-valence salt (CaCl2, CaBr2) environments and maintain their viscosifying performance is of great significance for the basic research on enriching deep and ultra-deep solid-free completion fluids. Summary of the Invention
[0006] To address the shortcomings of existing technologies, particularly the poor compatibility, insufficient high-temperature stability, and inadequate salt resistance of existing high-density solids-free completion fluid thickeners, this invention provides a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluids, its preparation method, and its application. The thickener of this invention exhibits high temperature resistance (≥180℃) and resistance to composite calcium salts (CaCl₂). 2 / CaBr2 can significantly increase the viscosity of completion fluid under high temperature conditions.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid includes the following steps:
[0009] (1) Synthesis of zwitterionic monomer A
[0010] (1.1) Hydroquinone (HQ) was added to a solution of isocyanate methacrylate (MOI) and mixed thoroughly. The resulting mixture was then added to a solution of dimethylaminoacetylhydrazine (DMAH) for reaction. After centrifugation, washing, and drying, an intermediate monomer was obtained.
[0011] (1.2) Add the intermediate monomer and hydroquinone (HQ) to tetrahydrofuran, stir to dissolve, and then add β-propiolactone to carry out the reaction; after filtration, washing and drying, zwitterionic monomer A is obtained;
[0012] (2) Preparation of high-temperature resistant zwitterionic polymer tackifier
[0013] Thermosensitive anionic monomer, acrylamide monomer, zwitterionic monomer A, and thermosensitive cationic monomer were added to deionized water, stirred evenly, and the pH of the system was adjusted to 7-8. Nitrogen gas was then purged to remove oxygen, and the temperature was raised to the reaction temperature. An initiator was added to carry out the reaction, and a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid was obtained.
[0014] According to a preferred embodiment of the present invention, the isocyanate ethyl methacrylate (MOI) solution in step (1.1) is obtained by dissolving isocyanate ethyl methacrylate in tetrahydrofuran, and the concentration of the isocyanate ethyl methacrylate (MOI) solution is 0.05-0.15 g / mL; the mass ratio of hydroquinone (HQ) to isocyanate ethyl methacrylate (MOI) is 1:80-120, more preferably 1:100.
[0015] According to a preferred embodiment of the present invention, the dimethylaminoacetylhydrazine (DMAH) solution in step (1.1) is obtained by dissolving dimethylaminoacetylhydrazine (DMAH) in tetrahydrofuran, and the concentration of the dimethylaminoacetylhydrazine (DMAH) solution is 0.05-0.1 g / mL; the mass ratio of dimethylaminoacetylhydrazine (DMAH) to isocyanate methacrylate is 1-1.5:2.
[0016] According to a preferred embodiment of the present invention, the temperature of the reaction in step (1.1) is 35-45°C, and the reaction time is 2-4 hours.
[0017] According to a preferred embodiment of the present invention, the washing in step (1.1) is washing with ether 3-5 times; the drying is vacuum drying at 70-90°C for 8-12 hours.
[0018] According to a preferred embodiment of the present invention, the mass ratio of hydroquinone (HQ) to the intermediate monomer in step (1.2) is 1:70-90, and more preferably 1:80.
[0019] According to a preferred embodiment of the present invention, the mass ratio of the intermediate monomer to the volume of tetrahydrofuran in step (1.2) is 0.05-0.1 g: 1 mL; and the stirring and dissolving temperature is 40-60 °C.
[0020] According to a preferred embodiment of the present invention, the mass ratio of β-propiolactone to intermediate monomer in step (1.2) is 1:3-3.5, more preferably 1:3.2; and the temperature for stirring and dissolving is 40-60°C.
[0021] According to a preferred embodiment of the present invention, the temperature of the reaction in step (1.2) is 40-60°C; and the reaction time is 8-12 hours.
[0022] According to a preferred embodiment of the present invention, the washing in step (1.2) is washing with ether 3-5 times; the drying is drying at 80-100°C for 8-10 hours.
[0023] According to the present invention, the structural formula of the obtained zwitterionic monomer A is shown in Formula I below:
[0024]
[0025] According to a preferred embodiment of the present invention, the antithermal anionic monomer in step (2) is 2-acrylamido-2-methylpropanesulfonic acid (AMPS), sodium vinyl sulfonate (VS), or sodium styrene sulfonate (SSS).
[0026] According to a preferred embodiment of the present invention, the acrylamide monomer in step (2) is N,N-dimethylacrylamide (DMAA) or N-isopropylacrylamide (NIPAM).
[0027] According to a preferred embodiment of the present invention, the thermoresistant cationic monomer in step (2) is dimethyl diallyl ammonium chloride (DMDAAC) or methacryloyloxyethyl trimethyl ammonium chloride (DMC).
[0028] According to a preferred embodiment of the present invention, the mass ratio of acrylamide monomer to deionized water in step (2) is 1:3-10.
[0029] According to a preferred embodiment of the present invention, the mass ratio of the thermo-resistant anionic monomer, acrylamide monomer, zwitterionic monomer A, and thermo-resistant cationic monomer in step (2) is 1-3:7:0.45-0.6:0.4-0.7, and more preferably 2:7:0.5:0.5.
[0030] According to a preferred embodiment of the present invention, the stirring rate in step (2) is 200-500 r / min, and the stirring time is 10-20 min.
[0031] According to a preferred embodiment of the present invention, in step (2), the pH of the system is adjusted to 7-8 using an aqueous sodium hydroxide solution with a mass fraction of 20%-40%.
[0032] According to a preferred embodiment of the present invention, the nitrogen deoxygenation time in step (2) is 20-40 min, and more preferably 30 min.
[0033] According to a preferred embodiment of the present invention, the initiator in step (2) is azobisisobutylamidine hydrochloride (AIBA), and the mass of the initiator is 0.1-1% of the total mass of the thermophilic anionic monomer, acrylamide monomer, zwitterionic monomer A and thermophilic cationic monomer.
[0034] According to a preferred embodiment of the present invention, the reaction temperature in step (2) is 50-60°C and the reaction time is 4-6 hours.
[0035] The present invention also provides a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid, which is prepared by the above preparation method.
[0036] According to the present invention, the above-mentioned high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid is used in composite calcium salt completion fluid; preferably, the concentration of the high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid is 15-20 g / L, and the composite calcium salt completion fluid has a density of 1.76 g / cm³. 3 A complex calcium salt solution, wherein the complex calcium salt comprises calcium chloride and calcium bromide.
[0037] The technical features and beneficial effects of this invention are as follows:
[0038] 1. The acrylamide monomers introduced into the zwitterionic thickener of this invention can significantly increase the molecular weight and temperature resistance of the product. The introduced anionic temperature-resistant monomer contains sulfonic acid groups with strong hydration ability, which enhances the stability of the polymer under high temperature conditions. The introduced temperature-resistant cationic monomer provides cationic groups, which can form a stable five-membered ring structure on the polymer molecular chain, further enhancing the rigidity of the polymer molecule. The introduced zwitterionic monomer A contains both carboxylic acid groups and ammonium ions, which can form a charge balance, giving the product an "anti-polyelectrolyte effect." Under high salt conditions, the molecular chain further expands, significantly increasing the viscosity of the composite calcium salt completion fluid. Moreover, the α-methyl group contained in zwitterionic monomer A increases the steric hindrance between polymer chains, which will cause the expanded polymer molecular chains to further form a stable network structure, significantly increasing the flow resistance of polymer molecules in the completion fluid, thereby achieving the effect of increasing the viscosity of the completion fluid.
[0039] 2. The anionic and cationic thermostable monomers used in this invention contain oppositely charged groups, making polymerization difficult under normal conditions. Therefore, this invention uses water-soluble azo initiators with high initiation efficiency, resulting in products with relatively high molecular weight and good water solubility. Although the five-membered ring structure formed by the cationic thermostable monomer can significantly improve the thermostable ability of the product, excessively high addition ratios increase the difficulty of the polymerization reaction and raise costs; while excessively low addition ratios result in products that cannot meet the thermostable requirements. The controlled addition ratios of anionic and cationic monomers within the range of this invention are the result of extensive experimental optimization.
[0040] 3. The zwitterionic thickener of this invention exhibits an "anti-polyelectrolyte effect," displaying unique "salt-responsive" properties. Under high-salt conditions, the molecular chains expand and form a stable network structure, thereby significantly increasing the viscosity of the composite calcium salt completion fluid. Even after rolling aging in a composite calcium salt environment at 180℃, it still exhibits excellent thickening performance and has broad application prospects in solid-free completion fluids. Detailed Implementation
[0041] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.
[0042] Furthermore, unless otherwise specified, the experimental methods described in the following embodiments are all conventional methods; and unless otherwise specified, the reagents, materials and equipment are all commercially available.
[0043] Example 1
[0044] A method for preparing a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid includes the following steps:
[0045] (1) 2 g of isocyanate methacrylate (MOI) and 1.5 g of dimethylaminoacetylhydrazine (DMAH) were dissolved in 20 mL of tetrahydrofuran (THF) to obtain isocyanate methacrylate solution and dimethylaminoacetylhydrazine solution, respectively. 0.02 g of hydroquinone (HQ) was added to the obtained isocyanate methacrylate solution and mixed well. The resulting mixed solution was added to the dimethylaminoacetylhydrazine (DMAH) solution and reacted at 40 °C for 3 h to form a white precipitate. The resulting reaction solution was centrifuged, and the white precipitate was washed three times with diethyl ether. The white solid obtained after washing was dried in a vacuum oven at 80 °C for 10 h to obtain the intermediate monomer. Weigh 1.6 g of intermediate monomer and mix with 0.02 g of hydroquinone (HQ), then add to 20 mL of tetrahydrofuran (THF) and stir to dissolve under a 50 °C water bath. Subsequently, add 0.5 g of β-propiolactone under stirring at 300 r / min and stir to react at 50 °C for 10 h. After the reaction is complete, filter the resulting reaction solution, wash the product three times with diethyl ether, and dry the resulting solid in a 90 °C vacuum oven for 8 h to obtain zwitterionic monomer A.
[0046] (2) Add 28g N,N-dimethylacrylamide (DMAA), 8g 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 2g dimethyl diallyl ammonium chloride (DMDAAC), and 2g zwitterionic monomer A to a beaker containing 160g deionized water. Stir continuously at 300r / min for 15min until homogeneous. Adjust the pH of the resulting mixture to 7 using a 20% NaOH aqueous solution. Transfer the mixture to a three-necked flask, purge with nitrogen for 30min, heat to 50℃, add 0.2g azobisisobutylamidine hydrochloride (AIBA), and react at 50℃ for 4h. Allow to cool naturally to room temperature to obtain a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid.
[0047] The structure of the high-temperature resistant zwitterionic polymer thickener for the composite calcium salt completion fluid obtained in this embodiment is shown in Formula II:
[0048]
[0049] Example 2
[0050] A method for preparing a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid is described in Example 1, except that the reaction temperature in step (2) is 55°C.
[0051] Example 3
[0052] A method for preparing a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid is described in Example 1, except that the reaction temperature in step (2) is 60°C.
[0053] Example 4
[0054] A method for preparing a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid is described in Example 1, except that the pH is adjusted to 8 in step (2).
[0055] Comparative Example 1
[0056] A method for preparing a polymer thickener for composite calcium salt completion fluid is described in Example 2, except that N,N-dimethylacrylamide is not added in step (2).
[0057] Comparative Example 2
[0058] A method for preparing a polymer thickener for composite calcium salt completion fluid is described in Example 2, except that the antithermal anionic monomer 2-acrylamido-2-methylpropanesulfonic acid (AMPS) is not added in step (2).
[0059] Comparative Example 3
[0060] A method for preparing a polymer thickener for composite calcium salt completion fluid is described in Example 2, except that the thermo-resistant cationic monomer dimethyl diallyl ammonium chloride (DMDAAC) is not added in step (2).
[0061] Comparative Example 4
[0062] A method for preparing a polymer thickener for composite calcium salt completion fluid is described in Example 2, except that zwitterionic monomer A is not added in step (2).
[0063] Comparative Example 5
[0064] A method for preparing a polymer thickener for composite calcium salt completion fluid is described in Example 2, except that: 8g of dimethyl diallyl ammonium chloride (DMDAAC) is added in step (2), and the mass ratio of antithermal anionic monomer to antithermal cationic monomer is 1:1.
[0065] Comparative Example 6
[0066] A method for preparing a polymer thickener for composite calcium salt completion fluid is described in Example 2, except that: 1g of dimethyl diallyl ammonium chloride (DMDAAC) is added in step (2), and the mass ratio of antithermal anionic monomer to antithermal cationic monomer is 8:1.
[0067] Comparative Example 7
[0068] A method for preparing a polymer thickener for composite calcium salt completion fluid is described in Example 2, except that 4g of zwitterionic monomer A is added in step (2).
[0069] Comparative Example 8
[0070] A method for preparing a polymer thickener for composite calcium salt completion fluid is described in Example 2, except that 1g of zwitterionic monomer A is added in step (2).
[0071] Comparative Example 9
[0072] A method for preparing a polymer thickener for composite calcium salt completion fluid is described in Example 2, except that in step (2), [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (SBMA) is used instead of zwitterionic monomer A.
[0073] Comparative Example 10
[0074] A method for preparing a polymer thickener for composite calcium salt completion fluid is described in Example 1, except that the pH is adjusted to 9 in step (2).
[0075] Comparative Example 11
[0076] Purchase the tackifier HE300 from a commercially available store.
[0077] Test case
[0078] The following tests were performed on the polymer tackifiers prepared in the examples and comparative examples.
[0079] 1. Determination of viscosity-average molecular weight of tackifier
[0080] Referring to the national standard GB / T 12005.10-1992 "Determination of Molecular Weight of Polyacrylamide by Viscosity Method", the flow time of the solvent (1.0 mol / L NaCl solution) and the solution were measured at 30℃ using a fully automatic capillary viscometer. The intrinsic viscosity number [η] of the thickener was calculated by combining the Huggins formula and the Kraemer formula, and the viscosity-average molecular weight Mη of the thickener was calculated using the empirical formula Mη=(10000[η] / 3.73)1.515.
[0081] 2. Effects of viscosifiers on the rheological properties and filtration performance of completion fluids before and after aging
[0082] Preparation of base solution:
[0083] Preparation of composite calcium salt completion fluid samples: Take 400 mL of deionized water, add 4 g (1%) of the viscosifier samples from the examples and comparative examples, and stir at 5000 r / min for 20 min at room temperature; then, slowly add 236 g of calcium chloride and 550 g of calcium bromide, and stir at 8000 r / min for 20 min at room temperature to obtain the composite calcium salt completion fluid with a density of 1.76 g / cm³. 3 ;
[0084] Aging treatment of completion fluid samples: The above completion fluid samples were placed in a roller heating furnace, and the aging temperature was set to 180℃ for 16 hours.
[0085] The rheological and filtration properties of the above-prepared solution were evaluated in accordance with GB16783.1-2014 "Field Testing of Drilling Fluids for Petroleum and Natural Gas Industry - Part 1: Water-based Drilling Fluids".
[0086] 3. Performance Test Results
[0087] Table 1 Viscosity-average molecular weight of tackifiers
[0088]
[0089]
[0090] Table 1 records the viscosity-average molecular weights of the samples from Examples 1-4 and Comparative Examples 1-11. It can be seen that among Examples 1-4, the sample prepared in Example 2 has a relatively high viscosity-average molecular weight. Comparative Example 1 did not add the acrylamide monomer N,N-dimethylacrylamide (DMAA), resulting in a low molecular weight of the product. Comparative Examples 2, 3, and 4 correspond to the absence of AMPS, DMDAAC, and SBMA monomers, respectively. It is evident that the lack of monomers leads to a decrease in the molecular weight of the tackifier. Comparative Examples 5, 6, 7, and 8 increased and decreased the proportions of thermophilic cationic monomers and zwitterionic monomers, respectively, resulting in unsatisfactory polymerization and failure to form larger molecular weights. Comparative Example 9 used [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (SBMA). Although the molecular weight increased compared to the previous comparative examples, it was still lower than the zwitterionic monomer A used in the examples of this invention. Comparative Example 10 changed the pH, resulting in a decrease in molecular weight. Comparative Example 11 used the commercially available tackifier HE300.
[0091] Table 2 Density 1.76 g / cm³ 3 Thickening properties of calcium chloride / calcium bromide brine after aging at 180℃
[0092]
[0093]
[0094] As can be seen from the test results in Table 2, compared with the composite calcium salt completion fluid without added thickener, the apparent viscosity (AV), plastic viscosity (PV), and dynamic shear force (YP) of the completion fluid were significantly improved after adding the thickeners prepared in Examples 1-5. Even after rolling aging at 180°C, the thickening performance of the examples could still be maintained, indicating that the thickeners prepared in the examples have excellent high-temperature resistance. Among them, the completion fluid sample with the thickener of Example 2 had the highest viscosity and the best performance.
[0095] In summary, the viscosity improver prepared by this invention still exhibits excellent viscosity improver properties after aging in a high-temperature (180℃) composite calcium salt (calcium chloride / calcium bromide) environment, which can enrich the development of high-temperature and high-density solids-free completion fluid technology.
Claims
1. A method for preparing a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid, comprising the following steps: (1) Synthesis of zwitterionic monomer A (1.1) Hydroquinone was added to the isocyanate methacrylate solution and mixed evenly. The resulting mixture was then added to the dimethylaminoacetylhydrazine solution for reaction. After centrifugation, washing and drying, the intermediate monomer was obtained. (1.2) Add the intermediate monomer and hydroquinone to tetrahydrofuran, stir to dissolve, then add β-propiolactone and react; after filtration, washing and drying, zwitterionic monomer A is obtained; (2) Preparation of high-temperature resistant zwitterionic polymer thickener Thermosensitive anionic monomers, acrylamide monomers, zwitterionic monomer A, and thermosensitive cationic monomers are added to deionized water, stirred evenly, and the pH of the system is adjusted to 7-8. Nitrogen gas is then purged to remove oxygen, and the temperature is raised to the reaction temperature. An initiator is added to carry out the reaction, resulting in a high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid. The thermosensitive anionic monomer is 2-acrylamido-2-methylpropanesulfonic acid, sodium vinyl sulfonate, or sodium styrene sulfonate. The thermosensitive cationic monomer is dimethyl diallyl ammonium chloride or methacryloyloxyethyltrimethylammonium chloride.
2. The preparation method of the high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid according to claim 1, characterized in that, The isocyanate methacrylate solution mentioned in step (1.1) is obtained by dissolving isocyanate methacrylate in tetrahydrofuran, and the concentration of the isocyanate methacrylate solution is 0.05-0.15 g / mL; the mass ratio of hydroquinone to isocyanate methacrylate is 1:80-120. The dimethylaminoacetylhydrazine solution is obtained by dissolving dimethylaminoacetylhydrazine in tetrahydrofuran, and the concentration of the dimethylaminoacetylhydrazine solution is 0.05-0.1 g / mL; the mass ratio of dimethylaminoacetylhydrazine (DMAH) to isocyanate methacrylate is 1-1.5:
2.
3. The preparation method of the high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid according to claim 1, characterized in that, The reaction temperature in step (1.1) is 35-45℃, the reaction time is 2-4h; the washing is 3-5 times with ether; the drying is vacuum drying at 70-90℃ for 8-12h.
4. The preparation method of the high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid according to claim 1, characterized in that, In step (1.2), the mass ratio of hydroquinone to the intermediate monomer is 1:70-90; the mass ratio of the intermediate monomer to the volume of tetrahydrofuran is 0.05-0.1 g:1 mL; and the stirring and dissolving temperature is 40-60℃. The mass ratio of β-propiolactone to the intermediate monomer is 1:3-3.5; the stirring and dissolving temperature is 40-60℃; the reaction temperature is 40-60℃; the reaction time is 8-12h; the washing is performed by washing with diethyl ether 3-5 times; and the drying is performed by drying at 80-100℃ for 8-10h.
5. The preparation method of the high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid according to claim 1, characterized in that, The acrylamide monomer mentioned in step (2) is N,N-dimethylacrylamide or N-isopropylacrylamide.
6. The preparation method of the high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid according to claim 1, characterized in that, The mass ratio of acrylamide monomers to deionized water in step (2) is 1:3-10; The mass ratio of the thermo-resistant anionic monomer, acrylamide monomer, zwitterionic monomer A, and thermo-resistant cationic monomer is 1-3:7:0.45-0.6:0.4-0.
7.
7. The preparation method of the high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid according to claim 1, characterized in that, The stirring rate in step (2) is 200-500 r / min, and the stirring time is 10-20 min; In step (2), the pH of the system is adjusted to 7-8 using a sodium hydroxide aqueous solution with a mass fraction of 20%-40%; nitrogen gas is passed through for deoxygenation for 20-40 minutes.
8. The preparation method of the high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid according to claim 1, characterized in that, The initiator mentioned in step (2) is azobisisobutylamidine hydrochloride, and the mass of the initiator is 0.1-1% of the total mass of the thermosensitive anionic monomer, acrylamide monomer, zwitterionic monomer A, and thermosensitive cationic monomer; The reaction temperature is 50-60℃, and the reaction time is 4-6h.
9. A high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid, characterized in that, It was prepared using the preparation method described in claim 1.
10. The application of the high-temperature resistant zwitterionic polymer thickener for composite calcium salt completion fluid as described in claim 9 in composite calcium salt completion fluid, characterized in that, The concentration of the high-temperature resistant zwitterionic polymer thickener used in the composite calcium salt completion fluid is 15-20 g / L, and the composite calcium salt includes calcium chloride and calcium bromide.
Citation Information
Patent Citations
Temperature-resistant microcross-linked tackifier and high-temperature-resistant solid-free water-based drilling fluid
CN104650827A
Preparation method of solid-free tackifying workover fluid for ultra-deep and ultra-high-temperature oil and gas well
CN114214049A
High-temperature-resistant polymer tackifier for calcium chloride brine completion fluid and preparation method of high-temperature-resistant polymer tackifier
CN118459660A
Ultrahigh-temperature-resistant and complex-salt-resistant amphoteric ion hydrophobic association polymer filter loss reducer and preparation method thereof
CN108715624A
Anti-calcium salt and temperature resistant tackifier and preparation method thereof
CN114426633A